Legislative Controls for Disciplinary Penalties Imposed on Public Servants: A Comparative Analysis of Jordanian and French Legal Frameworks - Al-Billeh, Tareq (Sriwijaya Law Review, 2025)
This study examines the legislative framework governing disciplinary penalties imposed on public servants under the Jordanian Civil Service Regulation of 2020 and the French General Civil Service Law of 2021. It seeks to analyze the concept of disciplinary punishment, its legal nature, and the fundamental principles that regulate its application within public administration. Additionally, the research explores the extent of judicial oversight exercised by administrative courts over disciplinary sanctions, ensuring compliance with legal and procedural safeguards. By adopting a comparative approach, the study highlights both the similarities and differences between the Jordanian and French legal systems concerning the imposition of disciplinary penalties and the mechanisms of judicial review applicable to such measures. The findings underscore that while administrative authorities possess discretionary power in selecting disciplinary measures, this discretion must be exercised within the confines of legality, adhering to the principle of proportionality. The study emphasizes that excessive or disproportionate penalties risk judicial intervention, reinforcing the necessity for fair and reasoned decision-making. Furthermore, the research concludes that disciplinary sanctions should be proportionate to the severity of the infraction, with administrative bodies ensuring a clear and precise definition of violations and their circumstances. This clarity facilitates effective judicial oversight and prevents arbitrary or overly punitive disciplinary measures, thus maintaining a balance between administrative authority and legal accountability.